OPTIMIZED SNR FOR INTER SYMBOL INTERFERENCE REDUCTION OVER MODIFIED DFZF EQUALIZER FOR PACKET ERASURE NETWORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
A novel technique presented in this paper is used to find an optimal signal to noise ratio (SNR) for maximizing overall data throughput and system performance for Automatic speech Recognition (ASR) applications. In speech data transmission over communication channels inter symbol Interference (ISI) will occur. In this paper the major problem faced while implementation is loss of data due to inter symbol Interference. By changing multiplying factor at feedback filter coefficients & Optimizing the signal to noise ratio, receiver errors can be minimized. DFZFE is used to combat ISI in wireless channels. In literature, purpose of designing the feed forward equalizer in the channel is treated linear. .A drawback of this method is error propagation due to the feedback.[15]. Feedback angle is found to maximize the output signal-to-noise ratio (SNR) [17]. Algorithm that achieves the same equalization performances at a reduced complexity are used [18]. Inter symbol Interference problem is faced in many applications such as cognitive radio, robotics, and sensor networks [19]